Longitudinal Validation of the PROMIS Physical Function Item Bank in Upper Extremity Trauma. Issue 10 (October 2017) - Kaat, Aaron J.; Rothrock, Nan E.; Vrahas, Mark S.; O'Toole, Robert V.; Buono, Sarah K.; Zerhusen, Timothy; Gershon, Richard C.
Abstract : Objectives: To evaluate the reliability, validity, and responsiveness of the Patient-Reported Outcomes Measurement Information System (PROMIS) Upper Extremity Computer Adaptive Test (UE-CAT) and the 8-item Physical Function short form (PF-SF8a) for monitoring outcomes after musculoskeletal injuries in upper extremity trauma patients. Design: Prospective cohort study. Setting: Two Level-I trauma centers. Patients: Eligible consecutive patients were approached and 424 consented at time 1 (median 9.7 weeks posttreatment). After 6 months, 132 patients (43% of the 307 eligible) completed follow-up measures. Intervention: Cross-sectional and longitudinal monitoring of upper extremity trauma patients treated with or without surgery. Main Outcome Measurements: Reliability, validity, and responsiveness of the UE-CAT and PF-SF8a. Internal consistency reliability, convergent validity correlations, and discriminant validity (by fracture severity and dominant/nondominant extremity groups) were calculated for PROMIS and non-PROMIS forms. Floor and ceiling effects were also examined at both assessment occasions. Responsiveness was evaluated using random-intercept mixed effects models and effect sizes. Results: PROMIS measures had excellent reliability, correlated well with legacy measures, and were responsive to treatment. Conclusions: PROMIS measures had good statistical properties. In addition to the known advantages of PROMIS, such as lower patient burden and the ability to assess the broadest range of functioning, our data demonstrated that for patients with upper extremity limitations, a region-specific measure such as the UE-CAT may perform more favorably than an overall/full body physical function measure. Abstract : Supplemental Digital Content is Available in the Text.